VOCATIONAL PEDAGOGY A DIMENSION OF VOCATIONAL LEARNING WITH WORKPLACE REQUIREMENT - Mohamad, Mimi Mohaffyza; Heong, Yee Mei; Kiong, Tee Tze; Rajuddin, Muhammad Rashid (Journal of Technical Education and Training, 2012)
Rapid changes are taking place in industry, the labor market, work to work organization. The changes of taking places in industry have an important implication for Vocational Education and Training (VET). These widespread changes have significant implications for the learning requirement of workers and for the pedagogical methods to facilitate that learning. This paper focuses in the learning of instructor, learners in the perspective of their readiness with teaching and learning challenge in VET. Some theoretical consideration in behavioral and cognitive psychology will be discussed derived from the concept of learning content vocational institutions; pedagogical strategies such as demonstration, practice and feedback implemented by the instructors for learning occur. The learners’ preferences based on their characteristics to cater their ability to learn in VET. Learners’ learning styles were investigated to identify their preferences in learning and match with the curriculum and practices in teaching VET. The shift in pedagogical orientation will focus in potential of individual, engage learners in development of their own vocational knowledge and skills. VET instructors and trainers must be able to recognize and adapt their teaching and learning practice in order to response to these needs.